Endemic parkinsonism: clusters, biology and clinical features - Menšíková, Katerina; Steele, John C; Rosales, Raymond; Colosimo, Carlo; Spencer, Peter; Lannuzel, Annie; Ugawa, Yoshikazu; Sasaki, Ryogen; Giménez-Roldán, Santiago; Matej, Radoslav; Tuckova, Lucie; Hrabos, Dominik; et al. (Nature reviews. Neurology, 2023)
The term 'endemic parkinsonism' refers to diseases that manifest with a dominant parkinsonian syndrome, which can be typical or atypical, and are present only in a particular geographically defined location or population. Ten phenotypes of endemic parkinsonism are currently known: three in the Western Pacific region; two in the Asian-Oceanic region; one in the Caribbean islands of Guadeloupe and Martinique; and four in Europe. Some of these disease entities seem to be disappearing over time and therefore are probably triggered by unique environmental factors. By contrast, other types persist because they are exclusively genetically determined. Given the geographical clustering and potential overlap in biological and clinical features of these exceptionally interesting diseases, this Review provides a historical reference text and offers current perspectives on each of the 10 phenotypes of endemic parkinsonism. Knowledge obtained from the study of these disease entities supports the hypothesis that both genetic and environmental factors contribute to the development of neurodegenerative diseases, not only in endemic parkinsonism but also in general. At the same time, this understanding suggests useful directions for further research in this area.
Keywords: Evropa; biologie; Phenotype; Europe; Humans; Biology; Guadeloupe; fenotyp; Parkinsonian Disorders; lidé; parkinsonské poruchy